Burn - Hardt, Helen (Hardt, Helen. Steel brothers saga, 2017)
"Jonah Steel is knee deep into trying to solve the mystery surrounding his family and his brother's abduction, and the arrival of his best friend has complicated the situation...although not as much as his infatuation with his brother's therapist, Dr. Melanie Carmichael. The quiet humility of the blond beauty has him enthralled, and he burns for her as he never has for any woman. Melanie Carmichael is intelligent and driven, yet filled with regret. She has fallen in love with gorgeous Jonah Steel, but fears she may never be able to tell him. The demons from her past have come for her...and she may not get out alive."--back cover.